The Impacts Of Political Unrest, Firm Specific And Macroeconomic Factors On The Financial Performance Of Insurance Industry In Ethiopia During Youth-Led Mass Anti-Government Protests (2014-2022) - Ademe Gebersilassie, Alemu (International Journal of Educational Research & Social Sciences, 2024)
This study investigates the impacts of political unrest; firm-specific and macroeconomic factors on the financial performance of the insurance industry in Ethiopia during youth-led mass anti-government protests. The study used, Return on Assets (ROA) and Return on Equity (ROE) as dependent variables. Eight key independent (internal and external) variables are also used. The study selected 17 out of 18 due to the availability of data for the period ranging from 2014 to 2022. The descriptive and multiple regression analyses were done. The results of the study indicate that political violence and terrorism (PV&T) have a negative and significant effect on ROA and ROE, while GDP has a positive and significant effect on ROA and ROE. The findings also show that financial risk (FR) has a negative and significant effect on ROA and ROE but a positive and significant effect on ROA and ROE. Furthermore, the study reveals that the size of company (SZ) and premium growth (PG) have a significant and positive impact on ROA but insignificant effect on ROE as well as liquidity (LQ) and asset tangibility (ATG) have a significant negative effect on ROE but insignificant effect on ROA. The inflation rate (INF) has no effect for both models on Ethiopian insurance financial performance. This study is considered one of the first pioneering studies that determined the factors affecting the financial performance of insurance companies in Ethiopia. Therefore, the study gives good insights to policymakers, regulators, and interested parties about enhancing the profitability of insurance companies in Ethiopia.